Studi Karakteristik Aliran di Jaringan Perpipaan Menggunakan Perangkat Lunak Epanet 2.0 (Studi Kasus di Laboratorium Teknik Mesin) - Kurniawan Rifai; Matheus M. Dwinanto; Wenseslaus Bunganaen (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Water is a basic human need both for the needs of daily life, starting from the need for drinking, cooking, and sanitation purposes. For this reason, it is necessary to plan and analyze the piping network in a building using either a gravity system or a pumping system. The mechanical engineering laboratory is one of the buildings within the Mechanical Engineering Study Program, Faculty of Science and Engineering, Nusa Cendana University which already has a piping network for distribution of clean water to the bathroom. However, until now this clean water supply has not utilized the reservoir with the existing tower near the laboratory. So, it takes software that can help, to determine the flow characteristics in the pipeline network. The piping network simulation method uses EPANET 2.0. The flow of water in the analyzed piping network is the reservoir to the bathroom. This research was conducted by analyzing the head and pressure in the piping network that will be installed in the Mechanical Engineering Laboratory using EPANET 2.0 software and analyzing losses in the pipeline network based on EPANET 2.0 software. The stability of the distribution of clean water, and the analysis period was carried out for 8 hours (extended period) with the condition of the water flow in each pipe in an open condition